Crystal Structure of the YAP‐binding Domain of Human TEAD1. (9th December 2018) - Mo, Yeajin; Lee, Hye Seon; Lee, Chang Hoon; Lim, Hwan Jung; Park, Seong Jun; Shin, Ho‐Chul; Kim, Cheol‐Hee; Kim, Seung Jun; Ku, Bonsu
Abstract :